Influência do laser de diodo na evaporação do solvente de sistemas adesivos em dentina. - Chiattone, Tatiana Dalla Costa (2015)
This study aimed to evaluate, in vitro, the influence of Diode Laser on the evaporation of adhesive systems solvent applied on the dentin. The groups were distributed in relation to the adhesive systems (Adper Single Bond 2, Adper Scotchbond Multi Purpose, Single Bond Universal, Clearfil SE Bond e Optibond All-in-one) and also to the technique for the evaporation of the solvent (air dry stream or Diode Laser). The degree of evaporation (GE) was determined through the measuring of mass loss through the gravimetric method in an analytical digital balance. To do so, a hundred human third molars had cavities class I made of following a pattern with the diamond burs # 4054 (KG Soresen, Barueri, SP, Brasil), under refrigeration, on which 10 μL were dispensed of each adhesive system, then one of the both techniques of solvent evaporation was applied: air dry stream, from a distance of 10 cm for each 5 seconds (control technique) or Diode Laser irradiated in a continuous mode perpendicularly and from a distance of 1 cm, in the power of 3 W in the interval of 30 seconds (experimental technique). To each one of the adhesive systems and to each one of the evaporation techniques ten monitoring repetitions were realized (n=10). Regarding the experimental technique, the measurements were realized from 5 to 5 seconds, up to 30 seconds. The variation between the initial mass (mi) and the final mass (mf) of the samples, respectively, before and after the application methods of evaporation proposed were turned into GE, by using the following equation: (mi-mf/mi)x100. In this way, to each time interval (5, 10, 15, 20, 25 and 30 seconds) it happened a calculated GE outcome. Those values were submitted to variance analysis (ANOVA) of two factors and Tukey s test as well. To the comparison between both of the evaporation techniques in each adhesive system a t-student test (α=5%) was realized. Basing on the obtained values of the GE, verified on the current study, it is possible to conclude that the irradiation with Diode Laser was capable of inducing the solvent evaporation of the tested adhesive systems, being superior to the control technique when used in the time of 30 seconds, excepted to the Optibond-all-in-one adhesive system.